The era of Seoul's rapid growth (1960s–1970s): The role of ex-military elite mayors. (March 2021) - Cho, Wonjun; Kwon, Youngsang
Abstract: This study aims to analyze the role of ex-military mayors in the development of Seoul after the Korean war (1950–1953). The six mayors of Seoul who took office under President Park (1961–1979) and the rapid development of South Korea, demonstrated excessive loyalty and drive to achieve policies established by Park's administration. It boded well for South Korea that three mayors, under the Park regime, had a military background. As a developing nation, it required rapid urbanization and industrialization to establish itself in the global space. This was significantly facilitated by the ex-military mayors. They re-developed the existing old downtown area and provided a number of infrastructures, and at the same time, they developed new towns in the southern part of the Han river that were relatively safe from North Korea's security threat. Furthermore, not satisfied with constructing new towns, they dispersed the city's core function in the newly urbanized areas, thereby developing the second and third CBDs of metropolitan Seoul, in order to be recognized by the dictator by showing their loyalty. As a result, their achievements contributed greatly in forming the basic urban structure of present metropolitan Seoul. Highlights: Role of ex-military mayors in the development of Seoul post 1953 is analyzed. State power is usually consolidated in the hands of the military elite. President Park appointed ex-military officials to ensure loyalty and efficiency. Corruption and unequal development were negatives of aggressive implementation. Such issues must be considered while constructing urban developmental policies.